Can psychiatry hinder intersubjectivity? A phenomenological critique of the biomedical conceptualization of anomalous experience - Wantoch, Sabina (Frontiers in Psychology, 2025)
This study examines the phenomenon of anomalous experiences. The term ‘anomalous experience’ refers to experiences often described as hallucinations and, more broadly, to the experiential dimensions of what is commonly referred to as psychosis. I present a critical analysis of the dominant clinical conceptualization of anomalous experience, which frames it as a ‘pathology of the mind’, by focusing on how this assumption is experienced intersubjectively. Drawing on Ratcliffe’s (2017) account of how intersubjectivity is implicated in anomalous experience, I argue that the psychiatric conceptualization of such experiences may obstruct intersubjective processes for those who undergo them. I suggest that this pathological marker, through its underlying assumptions and institutional practices associated with it, can give rise to a certain kind of relationality, characterized by an affective tone that excludes individuals from the shared interpersonal dynamics typically structuring experience in relation to a shared reality. Consequently, the psychiatric conceptualization of anomalous experience may play a role in the constitution of experiences of the kind that it seeks to erase. This implicates phenomenological psychopathology to question the starting assumptions that it takes as a given, direct picture of reality. Phenomenological psychopathology often adopts a pathological conceptualization of anomalous experience as its starting point, taking psychiatric concepts as given. I suggest that the discipline consider its own role, phenomenologically, in the multidirectional interactions that take place between anomalous experiences and the ways they are conceptualized and responded to. I propose that beginning with the direct experience itself, rather than its pathological association (and all the affective baggage this entails), would represent a progressive direction for the future of phenomenological psychopathology. This points toward critical phenomenology and critical phenomenological psychopathology.